2013
DOI: 10.1002/cncr.28516
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant interleukin‐2 in patients aged younger than 60 years with acute myeloid leukemia in first complete remission: Results from Cancer and Leukemia Group B 19808

Abstract: BACKGROUND Recombinant interleukin-2 (rIL-2) induces cellular cytotoxicity against leukemia blasts. Patients with acute myeloid leukemia (AML) in first complete remission (CR) may harbor minimal residual disease that is susceptible to rIL-2–activated effector cells. METHODS In the Cancer and Leukemia Group B (CALGB) 19808 study, patients with AML in first CR were randomly assigned after all planned chemotherapy to receive a 90-day course of subcutaneously administered rIL-2 or no further therapy. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Investigational use of drugs with alternative mechanisms of action remains of interest, but results have been disappointing with agents such as gemtuzumab ozogamicin 28,29 or, more recently, rIL-2 with or without histamine dihydrochloride. 16,3036 One study with rIL-2/histamine dihydrochloride showed a statistically significant DFS benefit but no benefit for OS; 35 however, a recent meta-analysis, plus a subsequent report of a randomized trial from the Alliance, further dampen enthusiasm for use of rIL-2 in remission maintenance in AML. 16,36 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigational use of drugs with alternative mechanisms of action remains of interest, but results have been disappointing with agents such as gemtuzumab ozogamicin 28,29 or, more recently, rIL-2 with or without histamine dihydrochloride. 16,3036 One study with rIL-2/histamine dihydrochloride showed a statistically significant DFS benefit but no benefit for OS; 35 however, a recent meta-analysis, plus a subsequent report of a randomized trial from the Alliance, further dampen enthusiasm for use of rIL-2 in remission maintenance in AML. 16,36 …”
Section: Discussionmentioning
confidence: 99%
“…16,3036 One study with rIL-2/histamine dihydrochloride showed a statistically significant DFS benefit but no benefit for OS; 35 however, a recent meta-analysis, plus a subsequent report of a randomized trial from the Alliance, further dampen enthusiasm for use of rIL-2 in remission maintenance in AML. 16,36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-leukemic activity of allogeneic HSCT relies not only on the effects of high dose chemotherapy or irradiation given during the conditioning regimen, but also on the immune-mediated graft-versus-leukemia effect [147–149]. The use of cytokines or pharmacologic agents to restore immune cell effector functions and, by extension, anti-leukemic effects represent other immunotherapeutic approaches that have been used in leukemia treatment [150153]. …”
Section: Acute Leukemiamentioning
confidence: 99%
“…On the contrary, the GG genotype and the G allele of the same polymorphism of IL-2 (rs2069762) are associated with higher risk of childhood lymphoma (Song et al 2012) as well as gastric cardia cancer (Wu et al 2009). There are also several reports on cancer immunotherapy with IL-2 in diverse types of cancers (Antony and Dudek 2010; Kolitz et al 2014;Guma et al 2014).…”
Section: Maternal Infections and Dysregulation Of Interleukins In Canmentioning
confidence: 99%